TINJAUAN PENGOLAHAN LIMBAH CAIR DI RUMAH SAKIT UMUM DAERAH MAJALAYA KABUPATEN BANDUNG - Setiawan, Qorina Apriliani; Irmawartini, Irmawartini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
The hospital is one of the places for treatment activities that produce large amounts of liquid waste and contain substances that are harmful to public health and the environment. The sampling technique in this study is purposive sampling to determine the quality of the physical liquid waste parameters , chemical , observation using a checklist made based on applicable regulations, and interview sheets to find out more information. in-depth study of wastewater treatment at the Majalaya Regional General Hospital. 07 of 2017. The volume of liquid waste in the hospital is 33.46 m3/day. The stages of processing liquid waste carried out are pre-treatment for liquid waste from the kitchen then entering the WWTP processing including the filtering process, after that it enters the equalization tank, contact tank, clarifier tank, filtration, then exits the outlet and enters the fish pond for distribution to a body of water.